2021
DOI: 10.1093/qjmed/hcab094.002
|View full text |Cite
|
Sign up to set email alerts
|

Role of Stem Cells in Treatment of Sensorineural Hearing Loss

Abstract: Background More than 5% of the world population lives with a hearing impairment. The main factors responsible for hearing degeneration are ototoxic drugs, aging, continued exposure to excessive noise and infections. The pool of adult stem cells in the inner ear drops dramatically after birth, and therefore an endogenous cellular source for regeneration is absent. Objectives The purpose of this study is to evaluate the role of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
0
0
Order By: Relevance
“…However, the garden cress seeds aqueous extract improved the deterioration in the kidney functions that induced by sodium nitrite in rats indicated by the increase the excretion of urea, creatinine, uric acid, sodium, chloride, total calcium and ionized calcium by increasing glomerular filtration rate. These results in agreement with many authors who reported the diuretic effects of the aqueous extract of garden cress seeds (Patel et al, 2009;Halaby et al, 2015), since it may be having nephroprotective and curative activity (Al Hamedan, 2010).…”
Section: Discussionsupporting
confidence: 92%
“…However, the garden cress seeds aqueous extract improved the deterioration in the kidney functions that induced by sodium nitrite in rats indicated by the increase the excretion of urea, creatinine, uric acid, sodium, chloride, total calcium and ionized calcium by increasing glomerular filtration rate. These results in agreement with many authors who reported the diuretic effects of the aqueous extract of garden cress seeds (Patel et al, 2009;Halaby et al, 2015), since it may be having nephroprotective and curative activity (Al Hamedan, 2010).…”
Section: Discussionsupporting
confidence: 92%